The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.11622/smedj.2020173
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of stillbirths based on different gestational thresholds at a tertiary hospital

Abstract: INTRODUCTION The stillbirth rate (SBR) is an important public health indicator. We studied the distribution of maternal and fetal characteristics and time trends of the SBR at KK Women’s and Children’s Hospital (KKH), Singapore, from 2004 to 2016 based on various definitions of stillbirth. METHODS Data was obtained from the Data Warehouse and Stillbirth Reporting System of KKH from 2004 to 2016. SBRs were calculated based on three definitions (fetal deaths at ≥ 20 weeks, 24 weeks or 28 weeks of gestation per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Fetal mortality rates can vary greatly depending on the socioeconomic and educational level of the country where the study is carried out. For example, a study conducted in nine hospitals in South Africa involving 9,811 pregnant women reported a fetal mortality rate of 15.5 per 1,000 births between 2017 and 2020 [ 26 ], while another study in a hospital in Singapore involving 157,039 pregnant women between 2004 and 2016 reported a fetal mortality rate of 5.1 per 1,000 births [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal mortality rates can vary greatly depending on the socioeconomic and educational level of the country where the study is carried out. For example, a study conducted in nine hospitals in South Africa involving 9,811 pregnant women reported a fetal mortality rate of 15.5 per 1,000 births between 2017 and 2020 [ 26 ], while another study in a hospital in Singapore involving 157,039 pregnant women between 2004 and 2016 reported a fetal mortality rate of 5.1 per 1,000 births [ 27 ].…”
Section: Discussionmentioning
confidence: 99%